Softening Among U.S. Smokers With Psychological Distress: More Quit Attempts and Lower Consumption as Smoking Drops - Kulik, Margarete C. (Am J Prev Med, 2017)
INTRODUCTION: It has been argued that as smoking prevalence declines, the remaining smokers represent a “hard core” who are unwilling or unable to quit, a process known as hardening. However, as recently shown, the general smoking population is softening not hardening (i.e., as prevalence falls more quit attempts and lower consumption among continuing smokers). People with psychological distress smoke more, so they may represent hard core smokers. METHODS: Using cross-sectional time series analysis, in 2016–2017 changes in quit attempts and cigarette consumption were evaluated over 19 years among smokers with serious psychological distress (Kessler-6 score ≥13) based on the National Health Interview Survey (1997–2015), controlling for sociodemographic variables. RESULTS: People with psychological distress had higher prevalence and consumed more cigarettes/day than people without distress. The percentage of those with at least one quit attempt was higher among those with psychological distress. The increase in quit attempts over time was similar among smokers in each of the distress levels. For every 10 years the OR of a quit attempt increased by a factor of 1.13 (95% CI=1.02, 1.24, p<0.05). Consumption declined by 3.35 (95% CI= −3.94, −2.75, p<0.01) cigarette/day for those with serious psychological distress. CONCLUSIONS: Although smoking more heavily than the general population, smokers with psychological distress, like the general population, are softening over time. To improve health outcomes and increase health equity, tobacco control policies should continue moving all subgroups of smokers down these softening curves, while simultaneously incorporating appropriately tailored quitting help into mental health settings.